CORRELATION NURSING WORKLOAD WITH THERAPEUTIC COMMUNICATION IMPLEMENTATION - Sulistyowati, Arlina Dhian; Rusminingsih, Esri; Prakosa, Wendhi (Universitas Airlangga, 2020)
Introduction: Therapeutic communication is communication between nurses and patient. Some cases and action done by nurses make nurses only focus on the action carried out without regard to therapeutic communication. This study aims to determine the correlation of nurses' workload with therapeutic communication in RSU Islam Klaten. Methods: The research design was correlation with cross sectional approach. The population in this study was inpatient room nurses. Questionnaire was used as the instrument to collect the data from the total 80 respondents which were taken as sample using the purposive sampling technique. The data was analyzed using Kendall tau. Results: Based on the research show that most respondents stated that work as a nurse did not become a workload of 66,3% and able to implement communication well at 63,8%. There was correlation between nursing workload with therapeutic communication with p value= 0,000. Consulsion: Based on the results analysis, there was a correlation between nursing workload with therapeutic communication implementation. The task rolling should be applied to avoid the workload and to conduct development of therapeutic communication training.